2019
DOI: 10.1111/gcb.14553
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐driven reduction of genetic variation in plant phenology alters soil communities and nutrient pools

Abstract: We examined the hypothesis that climate‐driven evolution of plant traits will influence associated soil microbiomes and ecosystem function across the landscape. Using a foundation tree species, Populus angustifolia, observational and common garden approaches, and a base population genetic collection that spans 17 river systems in the western United States, from AZ to MT, we show that (a) as mean annual temperature (MAT) increases, genetic and phenotypic variation for bud break phenology decline; (b) soil micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 105 publications
(135 reference statements)
4
43
1
Order By: Relevance
“…Genotypes with different phenologies may interbreed or adapt to have similar timing based on site conditions (Ware et al ) potentially making the extension of timing short‐lived. It may also be difficult to predict the exact timing of genotypes once moved to a new location due to phenotypic plasticity (Monty & Mahy ).…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes with different phenologies may interbreed or adapt to have similar timing based on site conditions (Ware et al ) potentially making the extension of timing short‐lived. It may also be difficult to predict the exact timing of genotypes once moved to a new location due to phenotypic plasticity (Monty & Mahy ).…”
Section: Introductionmentioning
confidence: 99%
“…Climate can impose selective pressures on heritable traits (Ware et al, ) such that genetically based trait‐climate response patterns might hint at the evolutionary dynamics occurring at species' niche limits. We found that common garden trait‐climate relationships showed some similar response patterns as field traits (Hypothesis 2), indicating the presence of genetic clines that constrain trait variation at climate niche limits.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SLA correlates with soil fertility at the global scale (Ordoñez et al, ), and soil factors can be important predictors of habitat suitability (Beauregard & de Blois, ; Coudun, Gegout, Piedallu, & Rameau, ). While it is beyond the scope of the present study, incorporating soil gradients into the double quantile approach is particularly important since plant traits both respond to and alter soil environments (Chapin, ; van der Putten et al, ), creating feedback effects that might boost or reduce plant performance at environmental limits (Van Nuland et al, ; Ware et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations